Determinant Of Cash Holding From Listed Company In Jakarta Islamic Index - Savilla Azzahra; Puji Sucia Sukmaningrum (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
Cash Holding has a crucial role in every firm. There is a lot of consideration why companies keep their cash on hand. These situations depend on motive of the firm and condition that they have faced. This study aims to determine the effect of leverage, liquidity, growth opportunity and firm size on firm cash holding. The sample of this study are listed firm from Jakarta Islamic Index (JII) from 2012-2019. The research method is quantitative, using Random Effect Model (REM). The number of observation reaches 80 data from listed firm in Jakarta Islamic Index during 2012-2019. Sources of data was provided in annual financial report from Indonesia Stock Exchange (IDX) or from official website. This study concludes that leverage and firm size has negative significant effect on cash holding while growth opportunity and liquidity have insignificant negative effect on firm cash holding.